2020
DOI: 10.3389/fimmu.2020.01205
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Virus-Induced Airway Immunity Dysfunction in the Pathogenesis of COPD Disease, Progression, and Exacerbation

Abstract: Chronic obstructive pulmonary disease (COPD) is the integrated form of chronic obstructive bronchitis and pulmonary emphysema, characterized by persistent small airway inflammation and progressive irreversible airflow limitation. COPD is characterized by acute pulmonary exacerbations and associated accelerated lung function decline, hospitalization, readmission and an increased risk of mortality, leading to huge social-economic burdens. Recent evidence suggests ∼50% of COPD acute exacerbations are connected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 118 publications
0
42
0
Order By: Relevance
“…The mechanism by which CYR61 associates COPD progression remains unclear. Numerous studies demonstrated that chronic airway inflammation aggravated lung function decline in COPD patients (5,29). On the other hand, several studies found that CYR61 had proinflammatory activities (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which CYR61 associates COPD progression remains unclear. Numerous studies demonstrated that chronic airway inflammation aggravated lung function decline in COPD patients (5,29). On the other hand, several studies found that CYR61 had proinflammatory activities (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Different viruses are implicated (e.g., rhinovirus, influenza, syncytial respiratory virus and coronavirus), being rhinovirus and coronavirus detected in 35.7% and 25.9% of viral infections occurring during these exacerbations (37). Typically, COPD patients are more susceptible to viral infections; the mechanisms involve dysregulated antiviral function of CD8 + T cells via the PD-1/PD-L1 axis and an altered production of interferons and chemokines (38). Thus, it is possible that the differences in protein plasma levels and their enrichment in viral related pathways observed in this study are the consequences of previous viral infections that induced lung inflammation and alterations on plasma proteome profile.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, COPD patients are more susceptible to viral infections. The mechanisms underlying this susceptibility included dysregulated antiviral function of CD8 + T cells via the PD-1/PD-L1 axis [59] and an altered production of interferons and chemokines [60]. Thus, it is possible that differences in protein plasma levels and the enrichment of differentially expressed proteins in viral related pathways (Figure 4) , could be the consequence of previous viral infections that induced lung inflammation and altered the plasma proteome profile in our COPD patients.…”
Section: Discussionmentioning
confidence: 99%